2003
DOI: 10.1580/1080-6032(2003)14[255:iawwra]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Injuries Associated With Whitewater Rafting and Kayaking

Abstract: Whitewater rafting and kayaking are growing exponentially in popularity, with almost 10 million rafters and 2 to 3 million kayakers, yet little has been published concerning the safety or hazards of these activities. This article reviews the demographics of such injuries and the types of injuries commonly encountered. Fortunately, fatalities are uncommon in these activities, with rafting and kayaking fatalities occurring at a rate of 0.55 and 2.9 per 100000 user days, respectively. Injury rates for kayaking an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 18 publications
0
28
0
Order By: Relevance
“…The majority were also male, aged in their 30 s and educated. This reflects the profile of visitors to United States of America (US) wilderness areas (Cole, 1996), together with those participating in adventure recreation such as 'traditional' rock climbing (McIntyre, 1991;Waldrup & McEwen, 1994), skiing (Edensor & Richards, 2007), white-water kayaking (Fiore, 2003) and cross-country mountain biking (Chiu & Kriwoken, 2003;TRC/EKOS, 2007). Also similar was that canyoners encompassed a wide age range (9e71), which paralleled the age range of US wilderness hikers (Shin & Jaakson, 1997).…”
Section: Visitor Profilesmentioning
confidence: 99%
“…The majority were also male, aged in their 30 s and educated. This reflects the profile of visitors to United States of America (US) wilderness areas (Cole, 1996), together with those participating in adventure recreation such as 'traditional' rock climbing (McIntyre, 1991;Waldrup & McEwen, 1994), skiing (Edensor & Richards, 2007), white-water kayaking (Fiore, 2003) and cross-country mountain biking (Chiu & Kriwoken, 2003;TRC/EKOS, 2007). Also similar was that canyoners encompassed a wide age range (9e71), which paralleled the age range of US wilderness hikers (Shin & Jaakson, 1997).…”
Section: Visitor Profilesmentioning
confidence: 99%
“…Experience has shown that equipment failure can result in hypothermia during excursions, but simple discomfort from body cooling is far more common with proper equipment upkeep [3840]. However, it should still be noted that uncomfortable body cooling has been shown to alter the perception of risk and even increase hazardous decision-making independent of hypothermia [41,42].…”
Section: Resultsmentioning
confidence: 99%
“…Adventure activities, such as white water (WW) canoeing, kayaking and rafting have shown to be especially popular [2][3][4]. Although popular, outdoor activities do carry a risk of injury or, in rare cases, death [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…However, WW paddling and rafting are associated with acute and chronic injuries [5,6]. Acute injuries are incidents of pain that occur rapidly due to a specific event or trauma.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation